FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENERIMAAN AUDITOR PADA KANTOR AKUNTAN PUBLIK DI SEMARANG - Nessya Dina Nurdiani; Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2013)
This study aimed to give empirical evidence concerning about criterias is needed by Recruiters for accepting auditors in the Public Accounting Firms upon Semarang city. Variable that used in this study were Subjective Qualifications, Interpersonal Attraction, Perceived Similarism, Objective Qualifications, Physical Attraction, Dress Effect, Gender, and Competency as Independent Variable with Hiring Decisions were Accepted and Rejected as Dependent Variable. This study used the empirical purposive sampling technique for collected the datas. The size of the sample in this study were 40 sample. Respondent in this study were Recruiters is Public Accounting Firms Semarang employees that participated in the intervew process and hiring decisions process of auditor. Data analyzis used analysis of logistic regression. The results of this study showed not all hypothesis were accepted. The results of the analysis showed factors were Subjective Qualifications, Perceived Similarity, Objective Qualifications, and Competency about hiring decisions process of auditor has signifficant and positive impact on accepted hiring outcomes. This was showed that Recruiters excited with applicant (auditor) who had positive criterias will have bigger chance to accept in Public Accounting firms on Semarang.